TEACHERS’ PERCEPTIONS OF THE USEFULNESS OF VOCABULARY PICTURE CARDS IN TEACHING ENGLISH VOCABULARY TO STUDENTS WITH INTELLECTUAL DISABILITIES - Agung Arif Hakim; Deasy Yunita Siregar; Achmad Ramadhan (Faculty of Tarbiyah nad Teacher Training, 2026)
English vocabulary learning is an important part of language development, especially for students with intellectual disabilities who often require concrete and visual learning support. Among various instructional media, vocabulary picture cards are widely used because they provide visual representations that may facilitate vocabulary learning. This study aimed to explore teachers’ perceptions of the usefulness of vocabulary picture cards in teaching English vocabulary to students with intellectual disabilities. The study employed a qualitative case study design involving one English teacher at a Special Needs School in Deli Serdang, Indonesia. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using thematic analysis. The findings revealed three major themes. First, picture cards were perceived as useful for attracting students’ attention, accelerating vocabulary understanding, and encouraging participation. Second, picture cards were considered feasible because they were practical, flexible, easy to combine with other teaching methods, and durable for long-term use. Third, several challenges were identified, including difficulties in visualizing abstract vocabulary, limitations in developing advanced communication skills, and maintaining students’ attention from boredom. Overall, vocabulary picture cards were perceived as valuable instructional media when integrated with broader teaching strategies.